(untitled) (Australia ; United States, 2008)
Contemporary Issues in Bioethics presents a breadth of issues and balanced coverage of the most important topics in bioethics, including human reproduction, euthanasia and assisted suicide, genetics, the right to health care, organ transplantation, human and animal research, and planning for threats to public health. With a diverse range of classic and contemporary essays written by scholars in bioethics and judges in landmark legal cases, this anthology will help you understand issues from a variety of perspectives
Keywords: Medical ethics.,Bioethics.,Y đức